2007
DOI: 10.1007/s10827-007-0030-1
|View full text |Cite
|
Sign up to set email alerts
|

Variability v.s. synchronicity of neuronal activity in local cortical network models with different wiring topologies

Abstract: Dynamical behavior of a biological neuronal network depends significantly on the spatial pattern of synaptic connections among neurons. While neuronal network dynamics has extensively been studied with simple wiring patterns, such as all-to-all or random synaptic connections, not much is known about the activity of networks with more complicated wiring topologies. Here, we examined how different wiring topologies may influence the response properties of neuronal networks, paying attention to irregular spike fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…The former is based upon the probability of quantal release, randomness of diffusion, and chemical reaction, or on the unpredictability of responses from ion channels within the synaptic cleft (Mainen and Sejnowski 1995;Stevens and Zador 1998;Rodriguez-Molina et al 2007). Vladimirski et al (2008) showed that noise-driven, unstructured networks require large, nonphysiological values of synaptic parameters in order to produce robust network bursts, while structured networks can use lower values for the same purpose (Kitano and Fukai 2007). To trigger spontaneous activity we simulated both network types, i.e., noise-and pacemaker-driven networks.…”
Section: Simulation Modelmentioning
confidence: 99%
“…The former is based upon the probability of quantal release, randomness of diffusion, and chemical reaction, or on the unpredictability of responses from ion channels within the synaptic cleft (Mainen and Sejnowski 1995;Stevens and Zador 1998;Rodriguez-Molina et al 2007). Vladimirski et al (2008) showed that noise-driven, unstructured networks require large, nonphysiological values of synaptic parameters in order to produce robust network bursts, while structured networks can use lower values for the same purpose (Kitano and Fukai 2007). To trigger spontaneous activity we simulated both network types, i.e., noise-and pacemaker-driven networks.…”
Section: Simulation Modelmentioning
confidence: 99%
“…Possibilities include largely distributed changes in structural (Cohen-Cory et al, 2010) and functional connectivity (Thomason et al, 2009). As connectivity determines neural network synchronization and dynamics (Lago-Fernández et al, 2001;Kitano and Fukai, 2007), synchronization may constitute a relevant mechanism by which BDNF affects cognitive functions. Such possible mechanisms have until now not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, we analyzed the dynamics of networks composed of both excitatory neurons and inhibitory neurons. A similar network has already been analyzed by Kitano & Fukai (2007), but, to our knowledge, this is the first report to show that the network topology required for the generation of synchrony is determined mainly by the dynamics of the inhibitory neurons.…”
Section: Resultsmentioning
confidence: 89%
“…All the networks treated in these works show global synchronization at p = 1. On the other hand, in some networks, the dependence of p 0 on the values of the parameters is not so much clear (LagoFernández et al, 2000;Masuda & Aihara, 2004;Netoff et al, 2004;Roxin, Riecke, & Solla, 2004;Kitano & Fukai, 2007). It is a future work to understand the relationship between the above two groups of studies.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation